The Humilitant Pedagogue: An Invitation to a Refractive Curricular Encounter - Piazza, Robert (Journal of the Canadian Association for Curriculum Studies, 2020)
The purpose of this auto-ethnographic study will be to explore and understand more fully how my experience of two educational events helped me discern between empty schooling and an educational education. I consider the theories of French philosopher Alain Badiou and their implications for English language arts curriculum and pedagogy. I hope to articulate what I will call a refractive curricular encounter as a contribution living within the traditions of reconceptualist curriculum theory, critical pedagogy and literary engagement. Such a refractive curricular encounter suggests breaking away from a given trajectory or set of coordinates; Badiou’s event does not interrupt or halt the world so much as interrupt the taken for granted knowledge and opinions, allowing the possibility of truths to emerge. As such, interruption is not static; interruption is vital and alive! I examine these truthful interruptions with a view to better understanding how neoliberal culture infiltrates my being so deeply as to have rendered my neoliberal and authoritarian urges invisible to me. My study also offers fruitful considerations for like-minded educators: how might framing education within an invitational context offer the possibility for an eventful-encounter to occur? Secondly, where Badiou suggests that the response to the emergent truth process ought to be one of a militant fidelity, I suggest that educators instead assume a disposition of what I call the humilitant teacher—a portmanteau of humility and militant. This paper explores the intersections of these notions and how they might offer insights into what it means to educate educationally.